NAMA DIRI PENDALUNGAN JEMBER DALAM KEBERMAKNAAN SOSIAL - Aryni Ayu Widyawati (Jantra., 2018)
This study looks at the toponym of Jember in relation to its history and the Pendalungan sub-culture–a mixture between Javanese and Madurese culture.This sub-culture is found in the Horseshoe area of East Java.The data were drawn from library research, observation, and interviews with various people, such as the local authorities, academicians, historians, andexperts in culture. The result of this study indicates that the Jemberese can have cross-cultural competence that has a bargaining position if they could “engineer” their cultural diversity both historically and aesthetically. Being the characteristics of people living the Horse shoe area, Pendalunganis an interesting research object which is still an open discourse. The role of the public, historians, and the government is needed to preserve the Pendalungan in Jember without changing the steady cultural order.